The use of dioxygen by HIF prolyl hydroxylase (PHD1). - McNeill, L; Hewitson, K; Gleadle, J; Horsfall, L; Oldham, N; Maxwell, P; Pugh, C; Ratcliffe, P; Schofield, C (2002)
The hypoxic response in animals is mediated by hydroxylation of proline residues in the alpha-subunit of hypoxia inducible factor (HIF). Hydroxylation is catalysed by prolyl-4-hydroxylases (PHD isozymes in humans) which are iron(II) and 2-oxoglutarate dependent oxygenases. Mutation of the arginine proposed to bind 2-oxoglutarate and of the 2His-1-carboxylate iron(II) binding motif in PHD1 dramatically reduces its activity. The source of the oxygen of the product alcohol is (>95%) dioxygen.